The Properties of Amyloid-β Fibrils Are Determined by their Path of Formation. Issue 13 (22nd June 2018) - Brännström, Kristoffer; Islam, Tohidul; Gharibyan, Anna L.; Iakovleva, Irina; Nilsson, Lina; Lee, Cheng Choo; Sandblad, Linda; Pamrén, Annelie; Olofsson, Anders
Abstract: Fibril formation of the amyloid-β peptide (Aβ) follows a nucleation-dependent polymerization process and is associated with Alzheimer's disease. Several different lengths of Aβ are observed in vivo, but Aβ1–40 and Aβ1–42 are the dominant forms. The fibril architectures of Aβ1–40 and Aβ1–42 differ and Aβ1–42 assemblies are generally considered more pathogenic. We show here that monomeric Aβ1–42 can be cross-templated and incorporated into the ends of Aβ1–40 fibrils, while incorporation of Aβ1–40 monomers into Aβ1–42 fibrils is very poor. We also show that via cross-templating incorporated Aβ monomers acquire the properties of the parental fibrils. The suppressed ability of Aβ1–40 to incorporate into the ends of Aβ1–42 fibrils and the capacity of Aβ1–42 monomers to adopt the properties of Aβ1–40 fibrils may thus represent two mechanisms reducing the total load of fibrils having the intrinsic, and possibly pathogenic, features of Aβ1–42 fibrils in vivo. We also show that the transfer of fibrillar properties is restricted to fibril-end templating and does not apply to cross-nucleation via the recently described path of surface-catalyzed secondary nucleation, which instead generates similar structures to those acquired via de novo primary nucleation in the absence of catalyzing seeds. Taken together these results uncover an intrinsic barrier that prevents Aβ1–40 from adopting the fibrillar properties of Aβ1–42 and exposes that the transfer of properties between amyloid-β fibrils are determined by their path of formation. Graphical abstract: Unlabelled Image Highlights: An intrinsic barrier prohibits Aβ1–40 to polymerize into amyloid fibrils of Aβ1–42 Aβ1–42 monomers readily incorporate into the fibrillar ends of Aβ1–40 Fibril-end cross-templating transfers properties from the parental seeds Cross-nucleation does not transfer properties of the parental seeds